Brutal serendipity: criminological Verstehen and victimization - Root, Carl (Critical criminology, 2013)
This article explores police use of force and its aftermath by focusing on the immediacy of police-citizen interactions via an autoethnographic account that invokes the concept of criminological verstehen. Specifically, the article explores issues of constructed meaning via Yuen’s interpretive constructs of ‘safe spaces’ and ‘creative analytic practice’ as a way of coming to terms with the first author’s lived experience of police brutality and its consequent legal process. Based on document analysis of official records such as police citations, medical files, and court transcripts, along with media accounts and the first author’s personal notes, the process of memoing provides an immersion into and an exploration of the data, and a tool for ascertaining meaning from it. Resultant themes of presentation of self, identity accomplishment, and silence are discussed in relation to the sorts of experiences and emotions necessary to a verstehen-oriented victimology. The article concludes with a discussion of the implications of this exercise in criminological verstehen.